PENGARUH KOMPENSASI TERHADAP SEMANGAT KERJA KARYAWAN (KASUS BAGIAN PRODUKSI PADA PT KEBUN PANTAI RAJA TELUK KUANTAN) - Arifandi, Bayu (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The importance of the provision of compensation is one way that made the company so that employees have a responsibility towards the company. The granting of compensation to the employee properly applied will reduce a sense of employee concerns against economic problems and daily needs, because they would have to comply with the compensation received by the company where he worked.Existing problems in this research Granting compensation do PT Kebun Pantai Raja Teluk Kuantangives rise to the existence of spirit and the excitement continued as an indication of the work of its employees. This makes PT Kebun Pantai Raja Teluk Kuantan continue to strive so that the compensation awarded can improve the morale and productivity of their employees. This research aims to: to know the granting of employee compensation part of the production on the Gulf Coast Gardens PT Kebun Pantai Raja Teluk Kuantan. employee morale to know the production at the Bay Gardens Beach PT Kebun Pantai Raja Teluk KuantanUntuk know how the compensation of employee morale the production at the Bay Gardens Beach PT Kebun Pantai Raja Teluk KuantanThe above results indicate that compensation given to the company as a whole is good whereas if viewed from each sub variables i.e. direct compensation was rated good. A compensation policy that is applied by the company is received by the employee. Whereas indirect compensation is already good, indirect compensation approved by employees. The incentive is good enough. Thus the incentives that are applied by the company PT Kebun Pantai Raja Teluk KuantanGardens approved quite well by employees, but there needs to be an increase in employee morale may again get better again, and for the morale of work productivity, showed less well.Thus the overall employee productivity less approved by the employees, which means that there needs to be improvement to improve employee morale was judged less good attendance rates, there are things â things that make employees less disciplined against regulatory acts of the company. Transfer of employees employee displacement rate is not good and the level of anxiety is pretty good, which means that employees still want to look for a better job in another company.Keywords: compensation, workforce, labour turn Over